A combined experimental and numerical approach for printed circuit rectangular microchannel J-T cooler using argon. (5th January 2021) - She, Hailong; Cui, Xiaoyu; Weng, Jianhua; Geng, Hui; Chang, Zhihao
Highlights: A novel J-T cooler with multi-layer, multi-rectangular microchannels was designed. The steady-state model for the J-T cooler was developed and verified. Printed Circuit Board (PCB) technology can change the performance of J-T cooler. The J-T coefficient analysis was carried out to optimize the performance. Abstract: Considering the small cooling capacity of a Hampson-type Joule-Thomson (J-T) cooler, a multi-layer printed circuit board (PCB) J-T cooler with parallel microchannels was fabricated and investigated in this study. The cooler has four parts: an inlet, a counter flow heat exchanger, a throttle, and an evaporator. A mathematical model is established and iteratively solved with a developed code. Using Ar as the working fluid, the cooling characteristics of the J-T cooler at 2–8 MPa were simulated. The pressure, temperature and velocity of the fluids as well as the temperature of the materials were obtained along the length of the cooler. The discrepancy between calculation and experiment of the cold end temperature is within ±2%, and the discrepancy of the outlet pressure is within ±4%, indicating the reasonability and reliability of the mathematical model. The model was also used to obtain the heat transfer rate between high- and low-pressure fluids, the enthalpy change, the cooling capacity of the cooler and the axial heat conduction of the material. The results show that the cold end temperature can reach 155.9 K with the gross cooling capacity being 3.66 W at the inlet pressure of 8.02 MPa. It was found that if the axial heat conduction is omitted, the cold end temperature could decrease further by 2.2 K. Finally, the optimisation measures of the cooler are discussed and proposed by analysing the variation law of the J-T coefficient.